Single-shot reconstruction of a subpicosecond pulse from a fiber laser system via processing strongly self-phase modulated spectra - Anashkina, E. A.; Andrianov, Alexey; Leuchs, Gerd (Results in Physics, 2020)
The single-shot reconstruction of an ultrashort pulse from a fiber laser system by the method based on recording and numerical processing of two self-phase modulated spectra after a nonlinear fiber is demonstrated experimentally. The 0.7-ps asymmetrical signal with an energy of 1 μJ retrieved by this method without time direction ambiguity is in good agreement with independent measurements by second harmonic generation frequency-resolved optical gating (SHG FROG) technique.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Intensity profile reconstruction; Kerr nonlinearity; Self-phase modulation; Single-shot pulse measurement